Muslims with Disabilities: Psychosocial Reforms from an Islamic Perspective - Ibrahim, Izaida (Journal of disability & religion, 2018)
Societal perceptions and attitudes toward people with disabilities vary from culture to culture. Negative perceptions of disabled people can cause them to be excluded and deprived of the right to live a full life. Muslims with disabilities live in a variety of different circumstances, whether in predominantly Muslim countries on low or average incomes, or as minority citizens, immigrants, or refugees in other countries; each person experiences unique challenges. Current psychosocial strategies have been ineffective in addressing these challenges. The influence of culture has negatively influenced the attitudes of society. The theoretical construct of disability from an Islamic perspective should be derived from the authentic teachings of Quran, Sunnah, and the stories of the Sahabi. The authors aim to explore the Islamic perspective on disabilities and strategies for psychosocial reform, based on the Quran, Sunnah, and Islamic history.